Optimalisasi Pelayanan Administrasi Publik Berbasis VLAN di Bidang TIK Polda Maluku - Rein Mars Solaulu; Aminah Bahasoan; Elake Nataniel (MAN 4 Kota Pekanbaru, 2026)
This study aims to determine and analyze the strategy for improving the quality of public administration services through the use of VLAN for information traffic at the Maluku Police ICT work unit. The research approach used is a qualitative approach. The informants of this study were members of the police at the Maluku Police ICT Work Unit. In addition, the author conducted in-depth interviews with key informants, namely the Head of the Maluku Police ICT Work Unit. Based on the results and discussion, it is concluded that the strategy implemented in improving the quality of public administration services through VLAN at the Maluku Police ICT Work Unit must focus on strengthening network security, improving HR competency, optimizing infrastructure, and mitigating cybersecurity risks and technical constraints. With a systematic approach and support from various parties, the use of VLAN can be an effective solution in improving efficiency, security, and transparency in public administration services in Maluku.